Desmoid-type fibromatosis: toward a holistic management - Penel, Nicolas; Kasper, Bernd; Graaf, Wilhelmina Tita Alide van der (Current opinion in oncology, 2021)
Purpose of review - Desmoid-type fibromatosis, a rare locally aggressive fibroblastic proliferation, is a treatment challenge. This review aimed to explore recent data about the management of desmoid-type fibromatosis. - Recent findings - New data underline the role of kinases and ɣ-secretase in stimulating cell proliferation and invasiveness in desmoid-type fibromatosis. This explains the proven activity of multikinase inhibitors (sorafenib or pazopanib) in the management of desmoid-type fibromatosis or the emerging role of a ɣ-secretase inhibitor. An international guideline for management was recently published, and this guideline take into account patient point of view. Lastly, recent studies highlight the multidimensional burden of desmoid-type fibromatosis, particularly health-related quality of life (HRQoL). - Summary - Active surveillance with planned MRI is the first-line management in desmoid-type fibromatosis. A site-specific and stepwise approach should be considered for progressive desmoid-type fibromatosis. Further, a risk-benefit analysis that considers the side effects and long-term sequelae should be conducted before deciding to start any treatment. A less aggressive approach should be considered. Multikinase inhibitors are effective, but their tolerability and side effects should be discussed with the patients. The symptoms and HRQoL should be integrated in decision-making. Desmoid-type fibromatosis patients should be offered support to address their needs supportive care.